2019
DOI: 10.1101/797464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revealing the molecular origins of fibrin’s elastomeric properties by in situ X-ray scattering

Abstract: Fibrin is an elastomeric protein forming highly extensible fiber networks that provide the scaffold of blood clots. Here we reveal the molecular mechanisms that explain the large extensibility of fibrin networks by performingin situsmall angle X-ray scattering measurements while applying a shear deformation. We simultaneously measure shear-induced alignment of the fibers and changes in their axially ordered molecular packing structure. We show that fibrin networks exhibit distinct structural responses that set… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Using synthetic images with known fiber dispersion confirmed that most of the tools, except for the Directionality plugin, performed well in the quantification of fiber alignment. We recommend a tool that returns a nematic order parameter, since this provides a sensitive measure between 0 and 1 that can be linked directly to theoretical models that connect fiber alignment to mechanical properties 34,58 . When also taking into account the ease of use of the tools and the possibility to adapt parameters, our preferences to quantify fiber alignment in fibrin networks go towards OrientationJ 27,59 (ImageJ plugin), CurveAlign 28 (MATLAB-based standalone application), or FiberFit 32 (Python-based standalone application).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using synthetic images with known fiber dispersion confirmed that most of the tools, except for the Directionality plugin, performed well in the quantification of fiber alignment. We recommend a tool that returns a nematic order parameter, since this provides a sensitive measure between 0 and 1 that can be linked directly to theoretical models that connect fiber alignment to mechanical properties 34,58 . When also taking into account the ease of use of the tools and the possibility to adapt parameters, our preferences to quantify fiber alignment in fibrin networks go towards OrientationJ 27,59 (ImageJ plugin), CurveAlign 28 (MATLAB-based standalone application), or FiberFit 32 (Python-based standalone application).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Figure V shows the 50 images with their corresponding nematic order parameter (S) as calculated by OrientationJ. OrientationJ was used as reference because of its proven sensitivity for fiber alignment 34 .…”
Section: Fiber Alignmentmentioning
confidence: 99%
“…Common methods to investigate the mechanical properties of cells within the ECM are tensile testing (Yang et al, 2015), and rheometry (Vos et al, 2020). The former is more common when investigating tissues like skin and bone, and the latter is more convenient when studying reconstituted systems or samples that are particularly soft.…”
Section: Experimental Approaches and Data Collectionmentioning
confidence: 99%